2017
DOI: 10.1039/c6cc08938k
|View full text |Cite
|
Sign up to set email alerts
|

Convenient route to tetraarylphosphonium polyelectrolytes via metal-catalysed P–C coupling polymerisation of aryl dihalides and diphenylphosphine

Abstract: A P-C bond-forming reaction has been applied to the convenient preparation of tetraarylphosphonium polyelectrolytes (TPELs) from aryl dihalides and diphenylphosphine. A TPEL having a thermal decomposition temperature of 460 °C that is also stable to heating at 65 °C in 6 M NaOH(aq) for at least 24 h has been prepared by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The proposed synthetic route for M1 was inspired by the Ni‐catalyzed P–C coupling route described by Cristau's group (Scheme ) . This method involved using an excess (∼5 equiv) of tolylbromide as solvent/reactant and heating at 200 °C for at least 24 h with ∼70% yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed synthetic route for M1 was inspired by the Ni‐catalyzed P–C coupling route described by Cristau's group (Scheme ) . This method involved using an excess (∼5 equiv) of tolylbromide as solvent/reactant and heating at 200 °C for at least 24 h with ∼70% yield.…”
Section: Resultsmentioning
confidence: 99%
“…This method involved using an excess (∼5 equiv) of tolylbromide as solvent/reactant and heating at 200 °C for at least 24 h with ∼70% yield. To decrease the amount of wasted aryl halide, shorten the reaction time, and improve the yield, we modified the procedure to include diisopropylamine as a base to facilitate the requisite deprotonation steps . Under these conditions, we found that the reaction was quantitative in ethylene glycol solvent after 15 h at 180 °C under N 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A metal‐catalyzed phosphorus–carbon coupling strategy involving aryl halides or aryl triflates with diphenylphosphine was recently utilized by Smith and co‐workers to prepare tetraarylphosphonium polyelectrolytes. The resulting PILs exhibited thermal stability up to 460 °C and reasonable alkaline stability …”
Section: Introductionmentioning
confidence: 99%